Studi Faktor Penerimaan Pengguna Terhadap Aplikasi SLIMS Di Perpustakaan MAN 2 Kediri: Analisis Model Modifikasi TAM" - Alif Fajar Bagus Akasyah; Eristya Maya Safitri; Anita Wulansari (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2023)
The aim of this research is to reveal the factors that influence the acceptance of the SLiMS application by users at the MAN 2 Kediri library, using a modified TAM model approach. In the analysis process, various variables are involved, including Perceived Usefulness, Perceived Ease of Use, Habit, System Quality, and Behavioral Intention to Use. The research method adopted a modified TAM approach with a sample of 297 respondents from a population of 1145 users. The main findings show that Habit (H) has a positive impact on Perceived Usefulness (PU) and Perceived Ease Of Use (PEOU). System Quality (SQ) has a positive impact on PU, but not on PEOU. Perceived Ease of Use (PEOU) has a positive impact on PU and Behavioral Intention to Use (BI). Perceived Usefulness (PU) has a positive impact on BI. The results of this research provide in-depth insight into the significant factors in the acceptance of the SLiMS application by MAN 2 Kediri library users using the modified TAM model. These findings may be useful in increasing the use of library applications and understanding how certain factors influence the acceptance of technology in educational settings.